TURN-TAKING FEATURES IN TONI TALKS: A CONVERSATION ANALYSIS - Bearis, Bena Jane I.; A. Parayno, Given; Tormes, Elaine Mae G.; J. Murillo, Filmor (SIGEH ELT : Journal of Literature and Linguistics, 2023)
This study is developed in order to determine the turn taking features in Toni talks to the use of conversation analysis. This study sought to answer two main questions: (1) What are the turn taking features that are observed in Toni talks under the life story and political theme category, (2) What are the similarities and differences of the turn taking features in the selected Toni talk’s episodes? To answer the research questions, the researchers used qualitative research design and in order for the data to be transcribed, the researchers utilized the Jefferson transcription system or the Jeffersonian transcription (2004) to yield the result of analysis. In conclusion, turn taking features such as mention, overlap, interruption, back channel, taking the floor/starting up, yielding the floor, and holding the floor was observed in this study as well as the features that was mostly utilized among the seven (7) turn taking features and how this substantiate the following Toni talks interviews. Results also explicated several key factors that motivate the utilization of the features, the similarities and differences of the chosen interviews, and the specific implications of the features in the course of the interviews.